(untitled) (Research, Society and Development, 2020)
Introduction: Congenital heart diseases are important malformations that compromise both patient survival and quality of life. These can be detected in the first days of life or intrauterine life. According to the Brazilian Society of Cardiology, cardiovascular diseases appear first among the causes of death in Brazil. Objective: to identify congenital heart diseases. Methodology: from the reading of the medical records of patients in a medium-sized pediatric hospital (years 2016 and 2018), Echocardiograms (ECO) and Electrocardiograms (ECG) were identified, which identified congenital heart diseases. Results: 163 medical records were selected, which patients underwent ECO and ECG, 70 for 2016 and 93 for 2018. The prevalence in both years: age group of children under 1 year of age and male (61.43% in 2016 and 58.07% in 2018). Of the total, 30.06% have some type of heart disease in their medical records (34.28% in 2016 and 26.88% in 2018), the most prevalent being Interventricular Communication (06 in 2016 and 08 in 2018). Conclusions: it was found that cardiovascular diseases represent a significant portion of the population served at this location. Early diagnosis allows for a timely and more accurate assessment in view of the need for intervention, the importance of this is verified so that an appropriate treatment is possible as soon as possible and thus, allowing a better prognosis allowing a prolonged survival of the individual. These data are expected to contribute to the reorientation of public policies aimed at health promotion.